Effects of midsole thickness on ground reaction force, ankle stability, and sports performances in four basketball movements - Teng, J.; Qu, F.; Shen, S.; Jia, S.-W.; Lam, W.- K. (Sports Biomechanics, 2022)
Changes in midsole thickness can influence cushioning and rearfoot stability in running, but no information has been established in basketball. This study aimed to investigate whether midsole thickness would alter ground reaction force, ankle stability and performance-related indicators in four basketball manoeuvres. Fifteen university basketball athletes performed lateral shuffle, forward sprint, counter-movement jump (CMJ) and drop landing in basketball shoes of five midsole thicknesses (Thinnest, Thin, Medium, Thick, Thickest). One-way repeated-measures ANOVA was performed on each of the biomechanics and performances variables and Friedman test was performed on comfort perceptions. Our findings found a significant midsole thickness effect on the lower extremity biomechanics (p < 0.05), with better traction (p = 0.019) and greater plantarflexion (p = 0.019) while sprinting with thinner shoe conditions. Thicker basketball shoes led to greater rearfoot inversion (p = 0.004) and a more significant inversion velocity peak (p = 0.019) during lateral shuffling. No significant difference in peak impact force or peak loading rate was observed between shoes during drop landing. These findings suggest that participants wearing basketball shoes with thicker midsole may lead to ankle instability during lateral shuffling manoeuvres. Wearing basketball shoes with thinner midsoles may be beneficial for sprint and jump performances.